Patients with Allan-Herndon-Dudley Syndrome (MCT8 deficiency) display symptoms of Parkinsonism in childhood and respond to Levodopa/Carbidopa treatment - Wilpert, Nina-Maria; Hewitt, Angela L.; Pons, Roser; Henke, Marie-Thérèse; Dell'Orco, Andrea; Bauer, Martin; Grolik, Christiane; Menz, Stephan; Wahle, Monika; Zink, Annika; Prigione, Alessandro; Reinauer, Christina; et al. (Movement disorders, 2025)
Background Patients with mutations in the monocarboxylate transporter 8 (MCT8, SLC16A2) suffer from X-linked recessive Allan-Herndon-Dudley syndrome (AHDS), which is characterized by developmental delay and a severe movement disorder. Current trials using thyroid hormone derivatives to overcome the transporter defect have failed to achieve patient-oriented therapeutic goals. Objectives Our aim was to define the type of movement disorder in AHDS in an observational cohort study and to investigate the causative role of the dopaminergic system. Methods We present longitudinal clinical data from the DEEPTYPE registry of 11 patients with video documentation, standardized phenotyping, cerebrospinal fluid (CSF) analysis, neuroimaging data, and the treatment response to levodopa/carbidopa supplementation. Results Children presented with signs of childhood parkinsonism, including hypokinesia, hypomimia, inability to sit or stand, rigidity, dystonia, and autonomic dysfunction. CSF homovanillic acid concentrations were decreased (n = 12), suggesting an isolated dopamine pathway impairment. Seven out of 8 patients responded favorably to l-dopa/carbidopa supplementation and we did not observe any adverse drug reactions. Conclusions AHDS is associated with childhood parkinsonism, which is linked with biochemical abnormalities of dopamine metabolism. It can be treated with l-dopa/carbidopa supplementation. However, further research is needed to elucidate the exact effect of MCT8 deficiency on dopamine metabolism.